Aquaculture and its conservation potential of critically endangered Jipe Tilapia (Oreochromis jipe) in Lake Jipe - Paul S Orina; Sheban Hinzano; Domitila Kyule; Abwao Jacob; Cecilia M Githukia; Tonny Orina; Mercy Chepkirui (Annals of Marine Science - Peertechz Publications, 2023)
Tilapia jipe (Oreochromis jipe) is listed as a critically endangered Cichlidae endemic to fast-shrinking Lake Jipe. Climate change and anthropogenic activities have significantly impacted the lakes' ecology and species' genetic integrity. Four months of Jipe tilapia culture growth performance was conducted in four selected farms within the Chala area, Taveta Sub-County of Taita Taveta County along the slopes of Mt. Kilimanjaro's Kenya side. The study assessed the growth performance of 3rd generation mixed-sex Oreochromis jipe under aquaculture conditions. Fish sampling was done monthly to assess the growth performance of fingerlings stocked at an average weight of 5 ± 0.02 g and a stocking density of 5/m3. Total weight ranged between 123.72 g, and 74.70 g from the entire growth trial sample population. The highest and the least mean weight gains recorded were 108.87 ± 4.31g and 87.12 ± 4.40g for Farm B and D respectively. Similarly, farm B recorded the highest mean length (18.80 ± 0.27) while farm C recorded the least (17.31 ± 0.25) with no significant difference between the selected farms. Water quality parameters were within the normally acceptable tilapia culture ranges. The study findings indicated a negative allometric growth (b < 3) for all farms except Farm A. All growth trials demonstrated a good Condition factor (K) with a range of 1.82 to 2.19. The present study concluded that O. jipe has the potential for aquaculture and species genetic conservation and restocking due to its ease of propagation. The study recommends further G x E breeding program strategies, nutritional and general management studies, and a policy limiting genetic material transfer from its catchment.